2020
DOI: 10.4183/aeb.2020.316
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor-Seeking Radiopharmaceuticals in the Diagnosis and Management of Adrenal Tumors

Abstract: Context.The variety of tumor-seeking radiopharmaceuticals, which are currently in clinical use, may have a potential role as imaging agents for adrenal gland tumors, due to physiological characteristics of this organ.Objective. The purpose of this study was to evaluate the diagnostic potential of 99m Tc-HYNIC-TOC, 99m Tc(V)-DMSA, and 99m Tc-MIBI in the assessment of adrenal tumors, by correlating with imaging findings and histopathologic results.Design. The research is designed as a crosssectional prospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Adrenal scintigraphy using 99m Tc-HYNIC-TOC is an SSTR-based imaging method, equal or superior to other conventional imaging methods. Encouraged by the results of various studies somatostatine radiolabeled analog 99m Tc-HYNIC-TOC has a high sensitivity in localizing adrenal tumors, while the visualization of functional adrenal masses remains controversial [15,41]. In the present study, we showed statistically significant positive diagnostic potential for detecting the existence of Ats and the functional active form of these tumors as well.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Adrenal scintigraphy using 99m Tc-HYNIC-TOC is an SSTR-based imaging method, equal or superior to other conventional imaging methods. Encouraged by the results of various studies somatostatine radiolabeled analog 99m Tc-HYNIC-TOC has a high sensitivity in localizing adrenal tumors, while the visualization of functional adrenal masses remains controversial [15,41]. In the present study, we showed statistically significant positive diagnostic potential for detecting the existence of Ats and the functional active form of these tumors as well.…”
Section: Discussionsupporting
confidence: 58%
“…MDCT examination is more frequently used, with a prevalence varying between 0.35% and 9% in different series, while MRI remains a second-level technique. The expense, the duration of examination, which is very demanding for the patient, as well as the appearance of artifacts caused by physiological processes in the abdomen, are cited as the main limiting factors [11][12][13][14][15]. The most important MRI technique is Chemical-shift which can be used to distinguish adenomas from non-adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations